Dampak Perubahan Kurs (Pass-Through Effect) terhadap Tujuh Kelompok Indeks Harga Konsumen di Indonesia - Achsani, Noer Azham; Nababan, Herry Frenky (UI Scholars Hub, 2008)
The impacts of exchange rate to an economy both domestically and internationally are an interesting discussion. One of the examples for discussion is exchange rate pass-through (ERPT). ERPT is defined as the rate of change of prices (domestic, imported or exported) as a result of change in exchange rate. Consumer price index (CPI) is one of the most frequent indicators used for measuring domestic price. This paper analyzes the impacts of exchange rate change (ERPT) to seven group of CPI in Indonesia. The Cholesky Decomposition is employed to identify structural shock of Structural Vector Autoregression (SVAR) which then combined with Vector Error Correction Model (VECM) for 48 time series units. The result shows that for the entire period there is an incomplete pass-through for the seven group of CPI. The largest effect occurs in the transportation and communication sector and food and beverages sector in which 35 percent of their changes in CPI are affected by change in exchange rate.